Carrier lifetime enhancement in halide perovskite via remote epitaxy - Jie Jiang (Nature Portfolio, 2019)
Crystallographic dislocation has proven harmful to the carrier dynamics in conventional semiconductors but it is unexplored in metal halide perovskites. Here Jiang et al. grow remote epitaxial perovskite films on graphene with density-controlled dislocations and confirm their negative impact.